Effect of eggshell fillers on the tensile and flexural properties of glass fiber reinforced polymer composites. (2022) - Muhammad, A.F.; Shukur Zainol Abidin, M.; Hassan, M.H.; Mustafa, Z.; Anjang, A.
Abstract: The natural bio-filler collected from waste such as chicken eggshells have been widely used as a value-added product in many applications. Recently, the utilization of eggshell bio-filler has also been found in polymer composites. This paper reports the effect of eggshell filler loading percentage and size on the tensile and flexural properties of glass fiber-reinforced polymer (GFRP) composites. Epoxy composite panels with four layers of plain-woven fabric of 800 gsm fabricated with 0 wt%, 10 wt%, 25 wt%, and 40 wt% eggshell powder (ESP) fillers using the wet hand lay-up technique. The chicken eggshells were dried, ground, and sieved into 53 μm and 150 μm filler size. The tensile and flexural tests were conducted according to ASTM D3039 and ASTM D7264. The tensile and flexural properties (both stress and modulus) were reduced with increasing filler loading from 10 wt% to 40 wt% for both filler sizes. The optimal filler loading has been achieved in 10 wt% of eggshell fillers for both filler sizes of 53 μm and 150 μm.